Preparation Specifics of Students-Philologists: Modern Technologies of Literary and Linguistic Text Analysis - Olivia, Ndjelassili; Shaklein, Victor (International Journal of Language Education, 2019)
The article is devoted to the trends and transformations of philological education in the context of modern technologies development. The purpose of the research is to study the preparation specifics of philology students and to develop a new approach to their training, based on an effective educational methodology of literary and linguistic analysis of the text. To achieve this goal, exercises and methods are defined. Such methods were used as: comparison, contextual-interpretative, comparative-historical method and other general scientific methods. The study found that in a globalized world it is necessary to form new core competencies in students-philologists, namely the capacity for independent learning throughout life and motivation. It is possible to achieve this through rethinking pedagogical methods. The authors proved that the text is an important means of modern communication which is dynamically transformed which determines the need for its deep philological research. For this, the authors improved the method of preparing students of philology which is based on the introduction of modern information technologies into the system of literary and linguistic analysis of the text. Software products such as Compleat Lexical Tutor and ABBYY Compreno, in particular Compleat Lexical Tutor, make the process of text analysis easy.